Developing Teaching Material of Vocabulary Through Singing For Seventh Grade of Islamic Junior High School of Hidayatus Sholihin - Cholifah, Nur; Huda, Miftakhul (Institut Agama Islam Negeri (IAIN) Kediri, 2020)
The research background was motivated by the difficulty of students in learning Arabic, basically in learning foreign languages, vocabulary is one of the three elements of language that is very important to master. This study aims to develop vocabulary teaching textbook with singing method in Mts Hidayatus Sholihin and see the effectiveness of the textbooks developed. The purposes of the research are: 1) The development of vocabulary Teaching textbook with singing method for seven grade of Mts Hidayatus Sholihin Gurah Kediri. 2) The application of vocabulary Effective Teaching texbook with singing method for seven grade of Mts Hidayatus Sholihin Gurah Kediri. The researcher used R&D research method by Borg and Gall which consist of 10 steps and data collection method used in the study was interview, questionnaires and tests. The research shows that: 1) The result of product development is Arabic teaching textbook for seventh grade students containing vocabularies arranged according to the tone of the song. The result of the expert validationts of the product as follows: the result from material expert is 83, 07%, results from media expert is 93, 84%, and the result from Arabic learning practitioner is 98, 33%. Based on exposure of the datas show that vocabulary learning by singing method declared very good. 2) The results of T-test show: the result of t-count between the pretest and popost-tes is 3,262 while the result of t-table is 2,015. Then it can be concluded t-count> t-table, then Ho is rejected and Ha is accepted, that is, there are difference outcome in learning vocabulary at seventh grade of Mts Hidayatus Sholihin between before and after using singing method. From the result of experimental it can be concluded the singing method in vocabulary learning at seventh grade of Mts Hidayatus Sholihin was declared